2020
DOI: 10.1002/macp.201900518
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐Stretched Double Network Polymer Films Based on Agarose and Polyacrylamide with Sensitive Humidity‐Responsive Deformation, Shape Memory, and Self‐Healing Properties

Abstract: A series of pre‐stretched double network (DN) polymer films based on agarose and polyacrylamide (Agar/PAM) are prepared. These films show the rapid and large deformation in response to humidity due to the release of contraction stress. The pre‐stretched dry film can curl toward the humidity direction into a scroll‐like structure in an extremely short time. The deformation direction can be also well controlled by the stretching direction. The released contraction stress increases with the increase of tensile st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Furthermore, natural pollen, corn xerogel, and agar have similar humidity-driven effects and are used to produce soft actuators. [60][61][62][63] Additionally, due to the advantages of material breathability and good heat dissipation properties, WR plant materials also performed well in the field of smart textiles. For example, Hu et al reported a self-balanced torsional actuator based on WR twisted bamboo yarns.…”
Section: Biological Material-based Actuatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, natural pollen, corn xerogel, and agar have similar humidity-driven effects and are used to produce soft actuators. [60][61][62][63] Additionally, due to the advantages of material breathability and good heat dissipation properties, WR plant materials also performed well in the field of smart textiles. For example, Hu et al reported a self-balanced torsional actuator based on WR twisted bamboo yarns.…”
Section: Biological Material-based Actuatorsmentioning
confidence: 99%
“…Furthermore, natural pollen, corn xerogel, and agar have similar humidity-driven effects and are used to produce soft actuators. 60–63…”
Section: Wr Material-based Actuatorsmentioning
confidence: 99%
“…It is well-known that polyethylene glycol (PEG) and poly­(acrylic acid) (PAA) are hydrophilic polymers. PEG- and PAA-based films show good humidity responsiveness. Coumarins are a kind of traditional perfume materials extracted from many plants. So far, more than 1000 coumarin derivatives have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The rational design and realization of smart materials are one of the fast-growing fields in materials science and engineering [1][2][3][4][5][6][7][8]. The functional materials with a controllable and intelligent response to external stimuli are of particular appeal and practical import, especially when the responsiveness is inherently incorporated in the materials [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This sort of actuators avoids the use of large optical, electric and magnetic fields that not only require sophisticated devices to generate but also may cause local heating to undermine the durability of materials. The humidity-driven actuators have been fabricated with various natural or artificial materials, including copy paper, π-stacked carbon nitride polymer, xerogel film, NaAlg-epoxidized natural rubber, cellulose nanomaterials, carbon nanotubes/shape memory polyurethane, paper derived from nature pollen, nafion-polypropylene-PDMS/graphite and agarose/polyacrylamide [5,[15][16][17][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%